Latent tuberculosis infection in the paradigm of the global tuberculosis control strategy (review) - Smilyanskaya, Maya; Suchanova , Lidiia; Volianskyi, Andriy; Kashpur, Nataliia (Annals of Mechnikov's Institute, 2022)
In recent decades, great changes have taken place in the epidemiology of tuberculosis (TB), which are reflected in the change in the statistical indicators of the spread of tuberculosis, due to both the infectious and social nature of the disease. At the end of the 20th century, after a long period of relative prosperity, the epidemiological situation with tuberculosis worsened significantly. Under the influence of various factors, there have been profound changes in human reactivity to the causative agent of tuberculosis, the causative agent itself has changed and, as a result, the incidence has increased, acutely progressive forms resembling "rapid consumption" have appeared, mortality has increased, the reservoir of detected tuberculosis infection has increased, problems such as drug-resistant tuberculosis, immunodeficiency. Although the efforts of scientists are focused on developing a new vaccine, this alone may not be enough to end the TB epidemic. Decisive public health action requires new diagnostic tools and therapeutic options, as well as a better understanding of the microbiological and clinical spectrum of TB infection and disease. Early diagnosis of tuberculosis infection implies, first of all, the detection of latent tuberculosis infection (LTBI), the interest of researchers in which increased at the end of the 20th century. Latent tuberculosis infection is defined as a state of a persistent immune response to antigens of Mycobacterium tuberculosis (MBT) that have previously entered the body in the absence of clinical manifestations of an active form of tuberculosis. According to WHO experts, about a quarter of the world's population has latent tuberculosis, including children. The risk that people infected with Mycobacterium tuberculosis will develop tuberculosis during their lifetime is 5-15%, and more often the disease can develop within the first five years from the moment of primary infection, mainly in childhood. The main goal of diagnosing latent TB infection is to provide preventive therapy to people at high risk of developing TB: “the intention to diagnose and treat”. One of the most important tasks in the therapy and diagnosis of TB is the ability to distinguish between latent tuberculosis and active TB and to determine the trigger factors for the transition from the first to the second state. The Mantu test with 2-5 tuberculin units of standardized purified tuberculin PPD (Purified Protein Derivate - purified protein derivative) is the main test for determining LTBI, the level of MBT infection in a population. Tuberculin diagnostics makes it possible to form groups of children with a high risk of developing tuberculosis for the purpose of early detection of the disease. Based on antigen-induced production of IFN in whole blood samples in the presence of MBT ESAT-6 and CFP-10 antigens, new tests have been developed to detect latent tuberculosis infection. These include IGRA tests, namely T-SPOT.TB. In a similar test system T-SPOT.TB, the amount of interferon-producing T-lymphocytes is determined. In recent years, IFN production-related studies (IGRAs) have been used in various clinical and epidemiological studies to detect tuberculosis disease or latent tuberculosis infection, and to replace or supplement the tuberculin skin test. Recent studies indicate the high informativeness of immunological tests (tests with the recombinant Tuberculosis allergen, ELISPOT, QuantiFERON®-TB Gold) in the differential diagnosis of post-vaccination and infectious allergies, as well as in the diagnosis of tuberculosis. Thus, the diagnosis of latent tuberculosis infection is not only mandatory, but also strategically necessary in the fight against tuberculosis. Today, thanks to the introduction of new immunological tests, it is possible to change the perception of the level of LTBI, as well as to identify groups at particular risk of developing active tuberculosis. In the last decade, the information content of new tests has been compared, which showed the need to use tests taking into account the immunological status of patients, in particular, the presence of HIV infection, etc. Changing approaches to the detection of LTBI, revising the issues of preventive examinations and activities in risk groups is necessary in the context of a high burden of tuberculosis and the emergence of new highly informative methods for early diagnosis of tuberculosis. Key words: tuberculosis, latent tuberculosis infection, diagnostics, immunological tests, risk groups. DOI: 10.5281/zenodo.6634750